The NKGB–NKVD Actions Against Polish Underground in Lithuania in 1944–1945 - Bubnys, Arūnas (Genocidas ir rezistencija, 1999)
The Soviet Union has never considered the Armija Krajowa (AK) its ally and made every effort to annihilate the armed underground movement of Poles in Lithuania. The process of the annihilation of Polish underground movement is generally divided into three periods. During the first period of the campaign in July 1944, the Soviets interned the AK units of the Vilnius and the Naugardukas districts. The Soviets arrested the district commandant A. Krzyzanowki, a number of commanding officers and about 7,900 soldiers. Nevertheless the Polish underground survived and continued its activities. During the second period between July 1944–February 1945, the NKVD-NKGB launched regular operations against Polish underground. The campaign reached its peak in December 1944–January 1945. At the time, the operations against armed resistance in Lithuania were directed by S. Kruglov, the NKVD assistant commissar. During this period NKVD troops transferred to and concentrated in Lithuania from other regions of the USSR and reinforced by a number of NKGB operatives handed a severe blow to the Polish underground. They arrested the executives of the AK staff and of the Government Commissioner’s office to the Vilnius District. Between December 20,1944 and February 6, 1945 the NKVD-NKGB arrested 9,249 Poles. After such big losses the process of gradual abatement of Polish resistance had started. Facing the Soviet terror many Poles of Lithuania decided to repatriate to Poland. During the third period from March 1945 until autumn of the same year the AK units had finally ceased their activities, and Polish partisans persuaded by the NKVD-NKGB reported themselves to Soviet authorities. The last Commandant of the Vilnius district Wincenty Chrząszczewsky- Ksawery was arrested on July 18, 1945. Between July 1944 and May 20, 1945 the NKGB arrested or detained 7,116 participants of the Polish underground and the activities of the AK in Lithuania were suppressed.